2017
DOI: 10.1016/j.cyto.2017.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Interferon regulatory factor signaling in autoimmune disease

Abstract: Interferon regulatory factors (IRFs) play critical roles in pathogen-induced innate immune responses and the subsequent induction of adaptive immune response. Dysregulation of IRF signaling is therefore thought to contribute to autoimmune disease pathogenesis. Indeed, numerous murine in vivo studies have documented protection from or enhanced susceptibility to particular autoimmune diseases in Irf-deficient mice. What has been lacking, however, is replication of these in vivo observations in primary immune cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 166 publications
0
27
0
Order By: Relevance
“…Limited and not very well-replicated studies have reported an association of IRF2 polymorphism with susceptibility to the autoimmune disease systemic lupus erythematosus (SLE). The SLE risk haplotype was suggested to be associated with activation of IRF2 ( 17 , 30 , 31 ).…”
Section: Implications For Irfs In Disease Pathogenesis–why Target Thementioning
confidence: 99%
See 2 more Smart Citations
“…Limited and not very well-replicated studies have reported an association of IRF2 polymorphism with susceptibility to the autoimmune disease systemic lupus erythematosus (SLE). The SLE risk haplotype was suggested to be associated with activation of IRF2 ( 17 , 30 , 31 ).…”
Section: Implications For Irfs In Disease Pathogenesis–why Target Thementioning
confidence: 99%
“…Similarly, IRF3 polymorphisms were found to be associated with SLE but controversy still exists regarding their role in susceptibility and pathogenesis ( 17 , 23 , 32 ). Studies in a Mexican mestizo cohort found that the rs2304206 gene variant associated with increased IRF3 expression in plasmacytoid dendritic cells (pDCs), with elevated type I IFN expression and dsDNA autoantibodies ( 32 ).…”
Section: Implications For Irfs In Disease Pathogenesis–why Target Thementioning
confidence: 99%
See 1 more Smart Citation
“…Several interferon regulatory factors (IRFs) have been implicated in autoimmunity 12 , 13 . Amongst the IRFs, IRF4 plays a fundamental role in T and B cells including IL-21 production, class switching, and PC differentiation 12 , 13 . The multifaceted role of IRF4 has been ascribed to its capacity to cooperate with multiple transactivators like the AP-1 family members, BATF and Jun, and the Ets protein PU.1 (ref.…”
mentioning
confidence: 99%
“…Authors highlighted that vast majority of studies, which supported the dual protective and adverse role in the susceptibility to development of autoimmune disorders, were conducted on irf-deficient mice models in vivo. Now, primarily researchers should pay attention to the role of impaired IRF system in patients' immune cell activity, especially in autoimmune diabetes [23]. There are no works confirming the occurrence of IRF4-IRF5 axis dysregulation in monocytederived cells in DM1 juveniles.…”
Section: Introductionmentioning
confidence: 99%